Determination of linear tafel region from piecewise linear regression analysis - Mohamed Noor, Noraini; Othman, Raihan; Mohd Hatta, Maziati Akmal; Ani, Mohd Hanafi (Electroactive Materials Society, 2014)
Tafel polarisation method is widely used in corrosion studies but relies heavily on the accurate extrapolation of the linear regions. To eliminate the ambiguity in the linear extrapolation, the present study develops a quantitative method based on piecewise linear regression analysis. In this method, the entire polarisation data is divided into small sub-intervals and variation in the regression coefficient and linearity coefficient values are observed. Consistency in these values serves as a quantitative indicator of the linear Tafel regions. The method described is then demonstrated in potentiodynamic polarisation measurement of Al/NaCl (0.5 M) and Zn/KOH (1 M) systems. The piecewise linear regression analysis positively identified the linear regions from the polarisation branches and thus provided more accurate corrosion parameters of the systems.